Sustainable, Continuous Improvement in Online Academic and Information Literacy Support. Issue 1 (2nd January 2019) - Rae, Sandy; Hunn, Margaret; Lobo, Ana
ABSTRACT: This paper builds on previous research that evaluated the impact of an embedded online academic and information literacy module into the learning management system (LMS) of a first-year university business course. The research findings concluded that the resource contributed to student success and helped to demonstrate the value of the library at Griffith University to the wider community. Since the original module was embedded into the LMS for a single course in 2014, the provision of these bespoke online modules has expanded. Data has been gathered over the years from 2014 to 2017 on unique users and page views of the modules. Usage has exploded from 4442 page visits by 910 unique users in one course in 2014, to 271, 556 page visits by 12, 456 unique users in 45 different courses in 2017. Whilst the learning analytics support the continued and increased provision of these resources, other issues around sustainability have arisen and need to be addressed. The aim of this paper is to examine how the use of an e-learning model can help address issues of sustainability that arise as part of supporting an online approach to academic and information literacy support.